HPV vaccination impact on a cervical cancer screening program: methods of the FASTER-Tlalpan Study in Mexico - Jorge Salmerón; Leticia Torres-Ibarra; Xavier Bosch; Jack Cuzick; Attila Lörincz; Cosette M Wheeler; Philip E Castle; Claudia Robles; Eduardo Lazcano-Ponce (Instituto Nacional de Salud Pública, 2016)
Objective. To outline the design of a clinical trial to evalu- ate the impact of HPV vaccination as part of a hrHPV-based primary screening program to extend screening intervals. Materials and methods. A total of 18,000 women aged 25-45 years, attending the regular cervical cancer-screening program in primary health care services in Tlalpan, Mexico City, will be invited to the study. Eligible participants will be assigned to one of three comparison groups: 1) HPV16/18 vaccine and hrHPV-based screening; 2) HPV6/11/16/18 vaccine and hrHPV-based screening; 3) Control group who will receive only hrHPV-based screening. Strict surveillance of hrHPV persistent infection and occurrence of precancerous lesions will be conducted to estimate safety profiles at different screening intervals; participants will undergo diagnosis confirmation and treatment as necessary. Conclusion. The FASTER-Tlalpan Study will provide insights into new approaches of cervical cancer prevention programs. It will offer valuable information on potential benefits of combining HPV vaccination and hrHPV-based screening to safety extend screening intervals.   DOI: http://dx.doi.org/10.21149/spm.v58i2.7790